Anticoagulation prescribing practice following ischaemic strokes in the setting of non‐valvular atrial fibrillation. Issue 10 (18th October 2021) - Tan, Shuangyue; Williams, Cameron; Choi, Philip
Abstract: It is well established that anticoagulation following an ischaemic stroke in the setting of non‐valvular atrial fibrillation is an effective means of secondary prevention. However, there is a lack of a solid evidence base to guide both the agent choice and the optimal timing in which to initiate anticoagulation therapy. The decision is complex, and consideration is required to balance the risks between recurrent strokes and potentially causing or exacerbating parenchymal haemorrhages. A clinical audit was performed at a high‐volume primary stroke centre looking at anticoagulation prescribing practices among neurologists. We found apixaban was by far the anticoagulation of choice for non‐valvular atrial fibrillation. The median time to anticoagulation initiation was Day 1 post transient ischaemic attack, Day 2 post small infarcts, Day 4 post moderate infarcts and Day 5 post large infarcts.